Review: Distribusi Bakteri Patogen oleh Lalat Sinantropik di Daerah Permukiman - Pranajaya, Condro Sukmo; Ginandjar, Praba; Hestiningsing, Retno; Yuliawati, Sri (Jurnal Ilmiah Mahasiswa, 2020)
Flies as mechanical vectors send pathogenic bacteria to food through contaminated body parts. Pathogenic bacteria can spread widely through contaminated body parts of synanthropic flies as well as flight ability. This study aims to describe the distribution of pathogenic bacteria by synanthropic flies in residential areas. This research is a literature review research with a simplified approach. Articles are collected through Google Scholar, Portal Garuda, Sciencedirect, Springer Link, Researhgate, and PubMed. Selected articles discuss the distribution of pathogenic bacteria by synanthropic flies in residential areas. Synanthropic fly species identified from the settlement are, Musca domestica, Chrysomya megacephala and Calliphora. Pathogenic bacteria identified from synanthropic flies in settlements are Salmonella typhi, Shigella, Escherichia coli, Campylobacter, Bacillus, Staphylococcus aureus, and Pseudomonas aeruginosa.. Genetically, there are similarities in bacterial isolates from flies and humans. Profiles of antibiotic resistant bacteria in flies in settlements match those from sewage treatment facilities. The presence of animals increases the risk of the spread of pathogenic bacteria by flies. There was no difference in E. coli bacteria in the fly at home and cage.. Genetic analysis of house fly populations and antibiotic resistant bacterial profiles showed the spread of flies between urban and rural areas. Synanthropic flies are able to spread pathogenic bacteria in settlements up to a radius of 2 km from the breeding site.